Dark Patterns and Unconscious Purchase Decisions: The Mediating Effect of Emotional Manipulation in Indonesian E-Commerce - Achmad Ridha; Hasnidar Hasnidar; Samsu Alam S (Candela Edutech Indonesia, 2026)
Dark patterns deceptive interface design techniques embedded in digital shopping platforms have attracted growing scholarly attention due to their capacity to subvert consumer autonomy. However, the psychological mechanism through which dark patterns translate into unconscious purchase decisions remains insufficiently theorised. This study examines the direct effect of dark patterns on unconscious purchase decisions and the mediating role of emotional manipulation in this relationship. Using a quantitative approach, data were collected via structured questionnaire from 220 active users of digital shopping platforms in Indonesia and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results indicate that dark patterns positively and significantly influence both emotional manipulation and unconscious purchase decisions. Emotional manipulation significantly mediates the relationship between dark patterns and unconscious purchase decisions, with the mediation type confirmed as partial. The model explains 61% of variance in unconscious purchase decisions. These findings extend deceptive design theory by foregrounding affect as a central mechanism of consumer exploitation and carry practical implications for platform regulation, digital consumer protection, and ethical interface design.